2006
DOI: 10.12973/ejmste/75435
|View full text |Cite
|
Sign up to set email alerts
|

Preservice and Experienced Biology Teachers' Global and Specific Subject Matter Structures: Implications for Conceptions of Pedagogical Content Knowledge

Abstract: ABSTRACT. This study aimed to describe preservice and experienced secondary biology teachers' global and specific subject matter structures (SMSs) and elucidate the relationship between these structures and teaching experience. Teachers' global and specific SMSs respectively designate their conceptions and/or organization of their disciplines and of specific topics within those disciplines. Two preservice and two experienced secondary biology teachers were chosen to participate in the study. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…Abd El-Khalick (2006), for example, argues that integrative models lack explanatory power, as no mechanism is suggested that shows how the interaction between SMK, pedagogy and contextual factors results in PCK. Banks et al (2005) suggest a teacher's -personal subject construct‖, which could be the missing link.…”
Section: Models Of Pck: Discussionmentioning
confidence: 99%
“…Abd El-Khalick (2006), for example, argues that integrative models lack explanatory power, as no mechanism is suggested that shows how the interaction between SMK, pedagogy and contextual factors results in PCK. Banks et al (2005) suggest a teacher's -personal subject construct‖, which could be the missing link.…”
Section: Models Of Pck: Discussionmentioning
confidence: 99%
“…Davis, Petish, & Smithey, 2006;Opwood & Souque, 1985) and PCK (e.g. Abd-el-Khalick, 2006;Appleton, 2003;Nilsson & Loughran, 2012) have been published both in other countries and in Finland (Palmberg, 2012;Palmberg, Jeronen, Svens, Yli-Panula, Andersson, & Jonsson, 2012;Palmberg, Jonsson, Jeronen, & Yli-Panula, 2016 ). We are unaware of any study that examines the issues, which this investigation is focused on.…”
Section: Introductionmentioning
confidence: 99%
“…knowledge on various subjects taught in the level of a particular class in a particular year and curricular vertical i.e. knowledge of what has been and what will be taught in the same subject in the following and previous years [40].…”
Section: Resultsmentioning
confidence: 99%